Retrospective Analysis of Blood Requisition Forms at a Tertiary Care Hospital - Asma Akhtar; Naureen Saeed; Faiq-un-Nisa (Proceedings)
Introduction: The blood requisition form functions as a vital communication link between requesting physicians and blood bank staff. The proper completion of blood request forms (BRFs) is a frequently overlooked aspect by clinicians and insufficient information or errors during the BRF completion process can significantly affect the quality of laboratory results and consequently impact patient outcomes, resulting in increased resource wastage and a higher risk of inappropriate therapy.